The R student companion - Dennis, Brian , 1952- (CRC Press, Taylor & Francis Group, 2013)
"Preface. R is a computer package for scientific graphs and calculations. It is written and maintained by statisticians and scientists, for scientists to use in their work. It is easy to use, yet is extraordinarily powerful. R is spreading rapidly throughout the science and technology world, and it is setting the standards for graphical data displays in science publications. R is free. It is an open-source product that is easy to install on most computers. It is available for Windows, Mac, and Unix/Linux operating systems. One simply downloads and installs it from the R website (http:// www.r-project.org/). This book is for high school and college students, and anyone else, who wants to learn to use R. With this book, you can put your computer to work in powerful fashion, in any subject that uses applied mathematics. In particular, physics, life sciences, chemistry, earth science, economics, engineering, and business involve much analysis, modeling, simulation, statistics, and graphing. These quantitative applications become remarkably straightforward and understandable when performed with R. Difficult concepts in mathematics and statistics become clear when illustrated with R. The book starts from the beginning and assumes the reader has no computer programming background. The mathematical material in the book requires only a moderate amount of high school algebra. R makes graphing calculators seem awkward and obsolete. The calculators are hard to learn, cumbersome to use for anything but tiny problems, and the graphs are small and have poor resolution. Calculating in R by comparison is intuitive, even fun. Fantastic, publication-quality graphs of data, equations, or both can be produced with little effort"-- Provided by publisher